Separation of Concerns in Mobile Hypermedia: Architectural and Modeling Issues - Challiol, Cecilia (2012)
Building Mobile Hypermedia and Web Applications is hard because of the myriad of concerns we need to face, such as those related to the specific application domain and those typical of mobile software. During the last years, we have been researching on modelling techniques for mobile hypermedia, and building infrastructure support for this and other kind of mobile and context aware software. In this chapter, we review the modelling features, design mechanisms and architectural support that we have developed to simplify the development process, and to obtain more flexible models and applications.